The Heterogeneous Effects of Workforce Diversity on Productivity, Wages and Profits - Andrea Garnero; François Rycx (Institute for the Study of Labor (IZA), 2013)
We estimate the impact of workforce diversity on productivity, wages and productivity-wage gaps (i.e. profits) using detailed Belgian linked employer-employee panel data. Findings, robust to a large set of covariates, specifications and econometric issues, show that educational (age) diversity is beneficial (harmful) for firm productivity and wages. The consequences of gender diversity are found to depend on the technological/knowledge environment of firms. While gender diversity generates significant gains in high-tech/ knowledge intensive sectors, the opposite result is obtained in more traditional industries. Overall, findings do not point to sizeable productivity-wage gaps except for age diversity.
Keywords: D24; J24; J31; M12; 330; labour diversity; productivity; wages; linked panel data; GMM